Conceptualization of Policy Adoption in Public Policy Areas - Lestari, Nanik; Keban, Yeremias T.; Kusumasari, Bevaola; Susanto, Ely (KnE Social Sciences, 2022)
This article aimed to review how the policy adoption process occurs based on published case studies, and explain the conceptualization of policy adoption, adding a theoretical overview to the conceptual definition. This study was conducted through a literature review. The researchers found 37 relevant articles to map the development of policy adoption. Qualitative descriptive analysis was used. Terms mapping was carried out using VoSviewer. Policy adoption was defined by general conceptualization. The findings showed that policy adoption is a part of the decision to choose policy alternatives after the policy formulation process. Mostly, the policy adoption process is influenced by internal and external determinants, often called policy diffusion. These determinants are each associated with elements that influence a government’s decision to adopt a policy. Keywords: policy adoption, public policy, policy diffusion